Epidemiology of diabetes mellitus in Russian Federation: clinical and statistical report according to the federal diabetes registry - Ivan Ivanovich Dedov; Marina Vladimirovna Shestakova; Olga Konstantinovna Vikulova (Сахарный диабет, 2017)
Aim. We analysed the main epidemiological characteristics of diabetes mellitus (DM) in the Russian Federation (prevalence, incidence, mortality and mean life span), degree of diabetes control, and prevalence of diabetic complications (retinopathy, nephropathy, and diabetic foot syndrome and macrovascular pathology) according to the federal DM registry. Materials and methods. The database of the federal DM registry of 79 regions was included using the online system until 31.12.2016. Results. TThe total number of patients with DM in the Russian Federation on 31.12.2016 was 4.348 million (2.97% of the population), comprising 4 million patients with DM2 (92%), 255,000 with type 1 diabetes (T1DM) (6%), and 75,000 with other types of DM (2%). DM prevalence per 100,000 population was as follows: T1DM, 164.19/100,000; type 2 diabetes (T2DM), 2637.17/100,000; and other types of DM, 50.62/100. The incidence per 100,000 population was as follows: T1DM, 16.15/100,000; T2DM, 154.9/100,000; and other types of DM, 8.65/100,000. Mortality per 100,000 population was as follows: T1DM, 2.1/100,000; T2DM, 60.29/100,000; and other types of DM, 0.57/100,000. Mortality decreased in patients with T1DM by 6.6% and with T2DM by 3.6%. Mean life span in patients with T1DM was 50.3 years for men and 58.5 years for women. Mean life span in patients with T2DM was 70.1 years for men and 75.5 years for women. Glycated haemoglobin A1c (HbA1c) levels in T1DM was <7% in 33.4%, 7%–7.9% in 28.3%, 8%–8.9% in 16.2%, and ≥9.0% in 22.1% of patients. HbA1c levels in T2DM was <7% in 52.1%, 7%–7.9% in 29.1%, 8%–8.9% in 10%, and ≥9.0% in 8.7% of patients. Conclusions. This study evaluated the increase in DM prevalence in the Russian Federation in 2016 and in the dynamics of 2013–2016, which was mainly due to T2DM. An increase in patients with a target HbA1c level <7% and a decrease in the proportion of patients with severe uncontrolled DM was observed; however, the treatment effectiveness of this key indicator was unsatisfactory, i.e. less than a third of the patients with DM. In the dynamics of 2013–2016, an increase in mean life span for patients with T2DM and mortality reduction in patients with T1DM and T2DM was observed. The frequency of diabetic complications varied widely, which may reflect differences in the quality of specialised care in different regions.